2019
DOI: 10.24926/iip.v10i2.1149
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescribing Habits in a Family Medicine Residency Program for the Management of Non-Cancer Pain

Abstract: Objectives: 1. List components of the 2016 CDC Guideline for Prescribing Opioids for Chronic Pain, 2. Describe the prescribing habits of medical residents and attending physicians within a family medicine residency program, 3. Discuss the direction of future research Methods: A report was generated for all patients with opioids listed as a medication at Christ Health Center family medicine clinic from July 2016 to June 2017. A total of 153 patients were identified with prescriptions written for chronic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…4 However, opioid prescribing practices of primary care clinicians often do not align with Centers for Disease Control Opioid (CDC) Prescribing Guidelines. 5,6 One family medicine residency program has demonstrated that an educational intervention utilizing guided instruction can be effective in improving residents' guideline adherence. 7,8 Other interventions have been studied in the past, but none have explored the qualitative and quantitative value of an interdisciplinary peer-review intervention in a residency program context.…”
mentioning
confidence: 99%
“…4 However, opioid prescribing practices of primary care clinicians often do not align with Centers for Disease Control Opioid (CDC) Prescribing Guidelines. 5,6 One family medicine residency program has demonstrated that an educational intervention utilizing guided instruction can be effective in improving residents' guideline adherence. 7,8 Other interventions have been studied in the past, but none have explored the qualitative and quantitative value of an interdisciplinary peer-review intervention in a residency program context.…”
mentioning
confidence: 99%